Implementation of Financial Accounting Standards for Small and Medium Entities in Berastagi SMES, Karo District - Yunita Pakpahan; Wina Theresia br Naibaho (Ilomata International Journal of Tax and Accounting, 2023)
This study aims to determine the application of accounting in Small, Micro and Medium Enterprises (MSMEs) and explain the barriers to business actors in applying accounting. This research is a descriptive qualitative research with data collection conducted through questionnaires and interviews. Object this research is MSME actors located in Berastagi District, Karo Regency. The data collected were 41 respondents using the purposive sampling technique. The results of the study show that most MSME actors do not know what to account for. The obstacle faced by business actors is the lack of socialization or training regarding accounting and SAK EMKM. The next obstacle is the lack of time to prepare financial reports, the assumption that financial reports are difficult to understand, and the low awareness of business actors to improve the presentation of financial reports by SAK EMKM